Linking Cork to Cork Oak Landscapes: Mapping the Value Chain of Cork Production in Portugal - Sørensen, Irene Holm; Torralba, Mario; Quintas-Soriano, Cristina; Muñoz-Rojas, José; Plieninger, Tobias (Frontiers in Sustainable Food Systems, 2021)
Traditional farming landscapes in South and Central Portugal, known as montados, are affected by global socio-economic and biophysical factors, putting the sustainability of the systems in jeopardy. Cork oak trees (Quercus suber L.) are characteristic features of these complex silvo-pastoral agroforestry systems, contributing with a globally important product, cork. The consequences of an increasingly distant, global scale of decision making on the local, landscape, scale. In this study, we use a value chain approach to test the concept that landscape products can ensure sustainable management of the landscape of origin. We interviewed agents – cork producers, intermediaries, industrial transformers, and winemakers – about the challenges they perceived in the business and how these were connected to the landscape of origin. We illustrate the network of agents and sub-actors involved in the sector and highlight the most prominent concerns. We conclude that this approach can reveal the major points for determining the future of the montado, and we suggest that collaboration amongst value chain agents collaborate can be a pathway to landscape sustainability.